EKSISTENSI PENGADILAN AGAMA DALAM MENGADILI PERKARA WARISAN - Mualifah Mualifah; Muhammad Faisal; Muhammad Jailani (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
Law No. 7 of 1989: “The Religious Court has the duty and authority to examine, decide and resolve matters in the first instance between Muslims in the field of marriage, inheritance, wills and grants made based on Islamic law and waqf and charity. The purpose in this study is to determine the application of Islamic inheritance law in resolving inheritance disputes in the Mataram Religious Court. The method used in this study is a normative legal approach that aims to analyze the decisions of religious courts related to inheritance cases. Aspects that will be studied are the application of Islamic inheritance law in the settlement of inheritance disputes and discrimination against women in Islamic inheritance law. The legal materials collected in this normative research are primary legal materials and secondary legal materials. The results show that as listed in article 49 paragraph 1 letter b, one of the "certain" areas of law that are included in the jurisdiction of the judiciary in the religious judiciary, adjudicate inheritance matters. Knowing the extent of the scope of this authority is very important, given the various issues of the point of contact of jurisdictional issues regarding inheritance matters between the general judiciary and religious judiciary in the past. Therefore, the output of this range through the approach of the provisions outlined in Law No. 7 of 1989 is to cover the Principles of Personality to Islam and the Vision of the Archipelago and covers all areas of Islamic inheritance law.